THE SHIFT IN SANTRIWATI’S BEHAVIOR AT AS’ADIYAH ISLAMIC BOARDING SCHOOL SENGKANG - Nurhalisa (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This research examines the behavioral shift of female santri at As’adiyah Islamic Boarding School Sengkang using a phenomenological and historical approach. The research employs a qualitative descriptive method with data collection techniques, including observation, interviews, and documentation. Data analysis follows the stages of collection, presentation, and conclusion drawing. The findings indicate a shift in santri behavior in terms of etiquette, dress code, rule compliance, and participation in extracurricular activities. The causes of this shift include internal factors such as the passing of Anre Gurutta, the presence of non-alumni teachers, and students being enrolled in the Islamic boarding school due to parental coercion. External factors include the influence of science and technology, which have reshaped santri’s mindset and behavior. To address these changes the Islamic boarding school has reinforced sincerity in seeking religious knowledge by reflecting on the struggles of Anre Gurutta, implementing the sami’na wa atha’na principle, and organizing seminars and commemorations of past scholars. The study’s implications emphasize the importance of preserving Islamic boarding school traditions in shaping the moral character of female santri and highlight the role of educators as role models. Additionally, this research encourages santri to contribute academic writings on Islamic boarding school ethics and moral values as references for the future development of As’adiyah Islamic Boarding School Sengkang